A Case of Canine Sinonasal Aspergillus fumigatus Infection Associated With Intracranial Extension and Temporal Myositis - Sarah E. Cox; Giulia Cattaneo; Oliver Russell; Ombeline McGregor; Andre Kortum (Veterinary Medicine and Science)
ABSTRACT A 12‐year‐old terrier was referred for investigation of a 4‐month history of coughing, sneezing and nasal discharge. Clinical findings were consistent with sinonasal Aspergillus fumigatus infection with evidence of intracranial extension on computed tomography. Endoscopic debridement followed by topical clotrimazole and systemic antifungal therapy resulted in clinical improvement. Magnetic resonance imaging after 4 weeks showed reduced intracranial disease but demonstrated evidence of temporal myositis. Repeated debridement and topical treatment were performed at 4 and 8 weeks in conjunction with long‐term voriconazole therapy. Further interventions were declined; the dog remains clinically well after 4 months with unilateral nasal discharge. As in human patients, invasive subtypes of sinonasal aspergillosis may also occur in dogs and be associated with poorer response to treatment.